Atherosclerosis: Clinical Perspectives Through Imaging - Taylor, Allen J.; Villines, Todd C.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Atherosclerosis: Clinical Perspectives Through Imaging is aimed at practicing clinicians and relies on didactic tabular and bullet points and a host of fine imagery describing the common features of the imaging of atherosclerosis, enabling the reader to understand more about the advantages and limitations of each modality in investigating athersclosis. Edited by and contributed to by a host of international experts in cardiac imaging, this book is a must read by all who image the heart.
Keywords: Medicine; Cardiology; Medicine & Public Health; Cardiology